"Evaluation of the Success of Permanent Molar`s Direct Pulp Capping Using MTA And Er;Yag laser " (Journal of Hama University, 2022)
Due to the complications of root canal treatment, conservative modalities to preserve pulp vitality are favorable. Direct pulp capping (DPC) refers to the coverage of the pulp tissue exposed by a biocompatible agent that can improve the prognosis of the tooth by 44% to 95 .This study aimed to clinically compare DPC with MTA alone and in combination with Er:YAG (erbium-doped yttrium aluminium garnet) laser irradiation (2940 nm).This clinical trial was conducted on 50 patients with a mean age of 20 years (in the range of 12 to 25 years) who required DPC following pulp exposure during deep caries removal. The teeth were divided into two groups. In the control group(includes 40 samples ), the teeth underwent DPC with MTA while in the test group(includes 40 samples), the teeth were first irradiated with a 2940 nm Er:YAG laser then underwent DPC with MTA. The patients were recalled at one, 3 ,6 and 9 months for the follow-up (clinical and radiographic examinations). The success rate was 87.5% in the laser group and 82.5% in the control group.No significant difference was found in terms of the success rate of DPC with MTA alone and in combination with Er:YAG laser irradiation